George E. Belknap papers - Belknap, George E. (George Eugene), 1832-1903.
Correspondence, articles, memoranda, and other papers relating to Belknap's naval career including his duty in the barrier forts at Canton (Guangzhou.), China, in the 1850s; combat duty in the Civil War; a tour of duty in Hawaii; and his command of the Asiatic Fleet. Subjects include hydrography; oceanography; old sea stories; social, economic, and political questions; and Belknap family affairs and genealogy. Correspondents include Daniel Ammen, John M. Brooke, Caspar F. Goodrich, Samuel W. Lowell, Francis Asbury Roe, George Collier Remey, and John A. Riddle.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Ammen, Daniel, -- 1820-1898 -- Correspondence; Brooke, John M. -- 1826-1906 -- Correspondence; Goodrich, Caspar F. -- 1847-1925 -- Correspondence; Lowell, Samuel W. -- Correspondence; Remey, George Collier, -- 1841-1928 -- Correspondence; Riddle, John A. -- Correspondence; Roe, Francis Asbury, -- 1823-1901 -- Correspondence; Belknap family; United States. -- Navy -- Foreign service -- China -- Guangzhou; United States. -- Navy -- Foreign service -- Hawaii; United States. -- Navy. -- Asiatic Fleet; Genealogy; Hydrography; Oceanography; Sea stories; United States -- Economic policy; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- Politics and government -- 19th century; United States -- Social policy; Naval officers